2003
DOI: 10.3354/ame032095
|View full text |Cite
|
Sign up to set email alerts
|

Fungal content and activities in standing-decaying leaf blades of plants of the Georgia Coastal Ecosystems research area

Abstract: Change in salinity, including expansion or contraction of salt-and freshwater marshes, due to altered river outflow may influence a variety of ecosystem processes, and the literature to date suggests that fungal activity in standing-decaying blades of macrophytes may be lower in freshwater marshes than in saltmarshes. I measured living-fungal mass (as ergosterol), rate of CO 2 evolution, and rate of fungal membrane synthesis (acetate incorporation into ergosterol) for standing-decaying blades from a series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Our data confirm the increase in microbial cell volume following submergence of dry litter in other studies (Newell 2003), which is likely due to the availability of moisture, a limiting factor for microbes in/on standing litter.…”
Section: Discussionsupporting
confidence: 81%
“…Our data confirm the increase in microbial cell volume following submergence of dry litter in other studies (Newell 2003), which is likely due to the availability of moisture, a limiting factor for microbes in/on standing litter.…”
Section: Discussionsupporting
confidence: 81%
“…Candau et al (1992) and Ferna´ndez-Martı´n et al (2000) showed that fungi can biosynthesize kaurene instead of ergosterol, which has been frequently used as a biomarker for fungi under nitrogen limiting conditions (e.g. Newell 2003;Nikolcheva et al 2003). In fact, ergosterol was not observed in these samples.…”
Section: Lipid Biomarkersmentioning
confidence: 90%
“…Filamentous fungi and yeasts are found in the oceans, but these heterotrophic eukaryotes do not appear to be abundant and are not ecologically important in aquatic ecosystems, except as decomposers of dry detritus from vascular plants in coastal regions (Newell 2003). Fungi and yeasts live on DOM or particulate organic detritus, and thus would have to compete with heterotrophic bacteria and archaea in the oceans.…”
Section: Marine Fungimentioning
confidence: 99%